Artemether-Lumefantrine versus Dihydroartemisinin-Piperaquine for Treatment of Uncomplicated Plasmodium falciparum Malaria in Children Aged Less than 15 Years in Guinea-Bissau - An Open-Label Non-Inferiority Randomised Clinical Trial. - Johan Ursing; Lars Rombo; Amabelia Rodrigues; Poul-Erik Kofoed (PLoS ONE, 2016)
Artemether-lumefantrine (AL) was introduced for treatment of uncomplicated malaria in Guinea-Bissau in 2008. Malaria then resurged and recurrent malaria after treatment with AL and stock-outs of AL were common. This study therefore aimed to assess the efficacy of AL and identify an alternative second line antimalarial. Dihydroartemisinin-piperaquine (DP) was chosen as it has been shown to be safe and efficacious and to reduce the incidence of recurrent malaria.In a multicentre randomised open-label non-inferiority clinical trial, AL or DP were given over 3 days to children aged 6 months-15 years with uncomplicated P. falciparum mono-infection. Intake was observed and AL was given with milk. Children were seen on days 0, 1, 2 and 3 and then weekly days 7-42. Recurring P. falciparum were classified as recrudescence or new infections by genotyping. Between November 2012 and July 2015, 312 children were randomised to AL (n = 155) or DP (n = 157). The day 42 PCR adjusted per protocol adequate clinical and parasitological responses were 95% and 100% in the AL and DP groups respectively, Mantel-Haenszel weighted odds ratio (OR) 0.22 (95% CI 0-0.68), p = 0.022. In a modified intention to treat analysis in which treatment failures day 0 and reinfections were also considered as treatment failures adequate clinical and parasitological responses were 94% and 97% (OR 0.42 [95% CI, 0.13-1.38], p = 0.15). Parasite clearance and symptom resolution were similar with both treatments.Both treatments achieved the WHO recommended efficacy for antimalarials about to be adopted as policy. DP was not inferior to AL for treatment of uncomplicated P. falciparum malaria in Guinea-Bissau.ClinicalTrials.gov NTC01704508.